Effects of grab bars and backrests on independent wheelchair transfer performance and technique. (9th November 2018) - Koontz, Alicia M.; Bass, Sarah; Kulich, Hailee; Cooper, Rory A.
Abstract: Objective: For individuals who rely on wheeled mobility devices for primary mobility, the ability to transfer independently greatly enhances participation in activities within and outside of the home. Nonlevel transfers are challenging and inevitable as not all surfaces in all settings can be made level with an individual's seat to floor height. The purpose of this study was to investigate the effects of two transfer aids, grab bars, and backrests, on the performance and quality of nonlevel transfers. Methods: This study employed a repeated‐measures design with transfer setup as the independent variable. Sixty‐eight (53 men and 15 women) wheeled mobility device users performed level and nonlevel transfers to a bare surface, a surface with grab bars present, a surface with grab bars, and a backrest present. For each condition, participants were asked to transfer as high and as low as they could go while still performing an independent and safe transfer. The transfer assessment instrument was used to evaluate the quality of their transfer technique. Results: Participants were able to transfer an absolute height up to 2.5 cm (1″) higher and lower when grab bars or grab bars and a backrest were present on the surface ( p  < 0.042) and 2.3 cm (~1″) higher relative to their wheelchair level seat high when grab bars were present on the surface ( p  < .001). Transfer technique significantly improved for both uphill and downhill transfers with the presence of grab bars and a backrest as shown by the transfer assessment instrument scores ( p  < 0.046). Conclusions: The presence of grab bars and a backrest on transfer surfaces may help mobility device users to achieve higher and lower absolute transfer heights and facilitate better transfer technique.